2022
DOI: 10.1002/jlcr.3958
|View full text |Cite
|
Sign up to set email alerts
|

Tritium hydrogen‐isotope exchange with electron‐poor tertiary benzenesulfonamide moiety; application in late‐stage labeling of T0901317

Abstract: The multifunctional radioligand [3H]T0901317 ([3H]1) has been employed as a powerful autoradiographic tool to target several receptors, such as liver X, farnesoid X, and retinoic acid‐related orphan receptor alpha and gamma subtypes at nanomolar concentrations. Although [3H]1 is commercially available and its synthesis via tritiodebromination has been reported, the market price of this radioligand and the laborious synthesis of corresponding bromo‐intermediate potentially preclude its widespread use in biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Based on our previous experience with HIE reactions on various substrates, we decided to test five iridium‐based C–H activation catalysts ( 7 – 11, Figure 3) that we deemed potentially suitable for the HIE reactions. They comprised the versatile homogenous Crabtree's ( 7 ) and Kerr‐type NHC catalysts [(cod)Ir (NHC)PR 3 ] ( 8 , 10 ) and [(cod)Ir (NHC)Cl] ( 9 ) as well as [Ir (OMe)(cod)] 2 ( 11 ) used for in situ generation of nanoparticles [26–28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous experience with HIE reactions on various substrates, we decided to test five iridium‐based C–H activation catalysts ( 7 – 11, Figure 3) that we deemed potentially suitable for the HIE reactions. They comprised the versatile homogenous Crabtree's ( 7 ) and Kerr‐type NHC catalysts [(cod)Ir (NHC)PR 3 ] ( 8 , 10 ) and [(cod)Ir (NHC)Cl] ( 9 ) as well as [Ir (OMe)(cod)] 2 ( 11 ) used for in situ generation of nanoparticles [26–28].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited heating capacity of our first‐choice solvent, DCM, which has a low boiling point (bp 40°C), we opted to test another chlorinated solvent, chlorobenzene (PhCl) (bp 132°C). Recent studies have shown that chlorobenzene provides a robust environment for facilitating HIE, even when using low‐reactivity substrates such as those with secondary and tertiary sulfonamide directing groups [26, 29, 30].…”
Section: Resultsmentioning
confidence: 99%